Profitability and Resource Use Efficiency of Polycarp Production in Morang, Nepal - Poudel, D.; Pandit, N. P. (Journal of the Institute of Agriculture and Animal Science, 2020)
The study was designed to portray the resource use efficiency of polycarp production in Morang district of Nepal during December 2017 to April 2018. Total of 30 commercial and 30 subsistence farmers were selected for primary data collection. Cobb-Douglas non-linear regression function was used to determine inputs that affect productivity. Empirical results illustrated the enterprise to be profitable as indicated by Benefit Cost Ratio, 1.87 in commercial and 1.33 in subsistence farms. The income of commercial farms was significantly higher (NRs. 76.94/kg) than subsistent farms (p<0.01). Estimates suggested feed and labor to be reduced; proper use of lime, fertilizer, other cost and pond rent to be increased. Therefore, the fishery enterprise is in the stage of higher potentiality to increase its production in the study area.